THE INFLUENCE OF REPUTATION, PERCEIVED VALUE, AND EWOM TOWARD PURCHASE DECISION THROUGH TRUST OF AIRBNB - Nabillah, Rosa; Kusumawardhani, Amie (Diponegoro Journal of Management, 2023)
ABSTRACT Airbnb is a traveling application that has been operated in Indonesia since 2016. However, since 2017 there has been an Airbnb controversy in Indonesia with Indonesian Hotel and Restaurant Association (PHRI) because Airbnb has received claims, it has disrupted the hospitality business in Indonesia. This has an impact on the movement of Airbnb's shares which are still low-momentum with an increase of only 3% from 2018 to 2021. Because Airbnb is still rarely used in Indonesia where there is data that reveals Traveloka is still the preferred travel application for booking accommodation in Indonesia in 2022, while Airbnb ranks fifth with 2%. This study uses people in Central Java Province who using Airbnb, then sampling is carried out using purposive sampling and has several criteria. The sample in this study was 150 respondents who live in Central Java, over 17 years of age, and have used Airbnb. The collected data will be analyzed using the structural equation model (SEM) method and processed with AMOS software. The result of this study indicates all hypothesis are accepted: Reputation, Perceived value, E-WOM has a significant positive effect on purchase decision and trust, and Trust has a significant positive effect on purchase decision.